Micro-focused Brillouin light scattering: imaging spin waves at the nanoscale - Sebastian, Thomas; Schultheiss, Katrin; Obry, Björn; Hillebrands, Burkard; Schultheiss, Helmut (Frontiers in Physics, 2015)
Spin waves constitute an important part of research in the field of magnetization dynamics. Spin waves are the elementary excitations of the spin system in a magnetically ordered material state and magnons are their quasi particles. In the following article, we will discuss the optical method of Brillouin light scattering (BLS) spectroscopy which is a now a well established tool for the characterization of spin waves. BLS is the inelastic scattering of light from spin waves and confers several benefits: the ability to map the spin wave intensity distribution with spatial resolution and high sensitivity as well as the potential to simultaneously measure the frequency and the wave vector and, therefore, the dispersion properties. For several decades, the field of spin waves gained huge interest by the scientific community due to its relevance regarding fundamental issues of spindynamics in the field of solid states physics. The ongoing research in recent years has put emphasis on the high potential of spin waves regarding information technology. In the emerging field of magnonics, several concepts for a spin-wave based logic have been proposed and realized. Opposed to charge-based schemes in conventional electronics and spintronics, magnons are charge-free currents of angular momentum, and, therefore, less subject to scattering processes that lead to heating and dissipation. This fact is highlighted by the possibility to utilize spin waves as information carriers in electrically insulating materials. These developments have propelled the quest for ways and mechanisms to guide and manipulate spin-wave transport. In particular, a lot of effort is put into the miniaturization of spin-wave waveguides and the excitation of spin waves in structures with sub-micrometer dimensions. For the further development of potential spin-wave-based devices, the ability to directly observe spin-wave propagation with spatial resolution is crucial. As an optical technique BLS do